Kondisi tutupan terumbu karang dan kelimpahan ikan karang famili Pomacentridae di perairan Pulau Talam Kabupaten Tapanuli Tengah Provinsi Sumatera Utara - Muhammad Rafli; Zulkifli Zulkifli; Thamrin Thamrin (Jurnal Zona, 2022)
This research was conducted in March 2022 in the waters of Talam Island, Central Tapanuli Regency, North Sumatera Province. This study aims to determine the condition of coral reef cover, abundance of reef fish family pomacentridae and the relationship between live coral cover and abundance of coral fish family pomacentridae in the waters of Talam Island. Coral reef cover data collection was carried out using the LIT (Line Intercept Transect) method, with a transect length of 50 meters and data collection for coral fish family pomacentridae using the UVC (Underwater Visual Cencus) method, with a transect length of 50 meters and a visibility limit of 2.5 meters to right and 2.5 meters to the left. Observations were made at three station points, each station at a depth of 4 m, 6 m and 8 m. Data depth of 4 m is considered to represent shallow waters, 6 m depth represents medium waters and 8 m depth represents deep waters. The results of this study indicate that the average percentage of live coral reef cover in the waters of Talam Island is 54.74% in the good category and the average abundance of coral fish family Pomacentridae is 4760 ind/ha with a total of 1071 individuals and is included in the abundant category. The results of simple linear regression analysis showed a correlation coefficient of 0.937 and a coefficient of determination of 0.8787.